Prevention of Status Epilepticus in Dravet Syndrome: Nationwide Survey in Japan - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Child neurologists and epileptologists at various university centers in Japan were surveyed by questionnaire to identify the most effective strategies for management of and prophylaxis against status epilepticus (SE) in children with severe myoclonic epilepsy in infancy (SMEI; Dravet syndrome), especially when associated with fever.